Candidate Species for Florida Aquaculture: Caribbean Spiny Lobster, Panulirus argus - Christian L. Miller; Cortney L. Ohs; R. LeRoy Creswell (EDIS, 2007)
FA147, a 5-page fact sheet by Christian L. Miller, Cortney L. Ohs, and R. LeRoy Creswell, introduces this lobster with whip-like antennae for aquaculture in Florida. It gives description and natural history and discusses culture methods, market, and diseases that may affect its aquaculture potential. Includes references and recommended additional reading Published by the UF Department of Fisheries and Aquatic Sciences, September 2007.